2011
DOI: 10.1016/j.jval.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of the Introduction of a Pre-Erythrocytic Malaria Vaccine into the Expanded Program on Immunization in Sub-Saharan Africa: Analysis of Uncertainties Using a Stochastic Individual-Based Simulation Model of Plasmodium falciparum Malaria

Abstract: We predict the effects of introduction of a pre-erythrocytic vaccine against Plasmodium falciparum into a malaria-endemic population in Africa. We use a stochastic simulation model that includes components of transmission, parasitology, and clinical epidemiology of malaria and was validated using the results of field trials of the RTS,S/AS02A vaccine. The results suggest that vaccines with efficacy similar to that of RTS,S/AS02A have a substantial impact on malaria morbidity and mortality during the first deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…9 and 10 and Additional file 2: Figures S16-S23). Previous analyses have found that public health impact of pre-erythrocytic vaccines will be highest at intermediate transmission intensities, where there are enough infections to make prevention worthwhile but where the parasite challenge is not so great as to drown the effect of the vaccine [9, 17]. The current analysis indicates that there is a strong general increase in impact with average level of transmission at the country level, indicating that in only a few countries (for example, Burkina Faso) are substantial proportions of the population in the range where vaccine effectiveness is compromised by an overwhelming parasitological challenge.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 and 10 and Additional file 2: Figures S16-S23). Previous analyses have found that public health impact of pre-erythrocytic vaccines will be highest at intermediate transmission intensities, where there are enough infections to make prevention worthwhile but where the parasite challenge is not so great as to drown the effect of the vaccine [9, 17]. The current analysis indicates that there is a strong general increase in impact with average level of transmission at the country level, indicating that in only a few countries (for example, Burkina Faso) are substantial proportions of the population in the range where vaccine effectiveness is compromised by an overwhelming parasitological challenge.…”
Section: Resultsmentioning
confidence: 99%
“…The reason is that a recommendation on the use of RTS,S is expected as early as the end of 2015. Previously the public health impact of introducing the RTS,S vaccine into routine vaccination schedules in Africa has been difficult to predict because available clinical trial data were inadequate for accurately estimating the kinetics of vaccine protection, and this uncertainty in the vaccine profile meant that geographically specific predictions of likely impact [17] were mainly of value to indicate general principles and data gaps. Site- and time- specific data from 18 months of follow-up of the Phase III trials [1] have now enabled us to estimate the vaccine profile accurately enough for quantitative predictions of impact at national level to have sufficient plausibility for guiding policy decision as well as for informing subsequent implementation decisions by ministries of health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this report, the use of RTS,S/AS01 could be highly cost-effective in many settings with low to moderate transmission, depending on the price of the vaccine and the duration of the vaccine's protection. 13 Malaria Vaccine Technology Road Map 2013 has envisaged the world as aiming for a licensed vaccine by 2030 that would reduce malaria cases by 75% and be capable of eliminating malaria.…”
Section: Current Status Of Vaccinementioning
confidence: 99%